2013
DOI: 10.1159/000353852
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Norovirus Associated with Sporadic Gastroenteritis among Children from the 2006/2007 to 2011/2012 Season in Nara Prefecture, Japan

Abstract: The present study aimed to describe the epidemiological characteristics of norovirus (NoV) associated with sporadic gastroenteritis in regional populations of Nara Prefecture, Japan, from the 2006/2007 to 2011/2012 epidemic season. Fecal specimens of sporadic gastroenteritis collected between September 2006 and August 2012 in Nara Prefecture were examined for the presence of NoV by reverse transcription-polymerase chain reaction. The NoV genotype was determined by nucleotide sequence analysis. In total, 274 No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…In contrast, the detection rate of HAstV among the 6 seasons was lowest during the 2010/2011 season (1.4z) and highest during the 2011/2012 season (7.3z). These rates were low when compared with the previously reported detection rates of NoV or RVA in Nara Prefecture (7,13). However, a total of 111 strains were detected, and these viruses were present during all the 6 seasons studied.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…In contrast, the detection rate of HAstV among the 6 seasons was lowest during the 2010/2011 season (1.4z) and highest during the 2011/2012 season (7.3z). These rates were low when compared with the previously reported detection rates of NoV or RVA in Nara Prefecture (7,13). However, a total of 111 strains were detected, and these viruses were present during all the 6 seasons studied.…”
contrasting
confidence: 77%
“…The annual observation period of gastroenteritis in the current study began in September and ended in August of the following year. Viral RNA was extracted as previously described (7). Reverse transcription-polymerase chain reaction (RT-PCR) was performed to screen for SaV and HAstV using SV-F11 and SV-R1 primers for SaV (8) and AC1?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks most frequently occur during cold weather (Ahmed et al, 2013;Lopman et 53 al., 2009;Mounts et al, 2000), and this seasonality is also observed in Japan (Mounts et al, 2000;Siebenga et al, 2009;Yoneda et al, 2014). Noroviruses are classified into five genogroups (GI-GV), which are further subdivided into at least 35 genotypes (Centers for Disease Control and Prevention, 2011;Zheng et al, 2006).…”
Section: Introductionmentioning
confidence: 85%
“…Although several comprehensive articles have reported on the prevalence, genotype seasonality, and outbreaks of gastroenteritis viruses in Japan, no systematic literature reviews and meta‐analysis have been published. Many research articles reporting on several kinds of diarrheal viruses throughout Japan showed the prevalence of diarrheal viruses ranging from 30.2% to 70.4% [Iritani et al, ; Phan et al , ,, ; Akihara et al, ; Shimizu et al, ; Harada et al, ; Kitahori et al, ; Nakanishi et al, ; Kawada et al, ; Yoneda et al, ; Thongprachum et al, ]. Most recently, a 4‐year study of the viruses that caused diarrhea in Japanese pediatric outpatients revealed the prevalence of diarrheal viruses at 70.4% [Thongprachum et al, ].…”
Section: Overview Of Diarrheal Virus Detectionsmentioning
confidence: 99%